Analysis Of Meaning Accuracy In The Translation Of Malay To Arabic Sentences Among Among Students Of Universiti Sains Islam Malaysia - Arnida A. Bakar; Lubna Abd. Rahman; Wahida Mansor (Usuli Faqih Research Centre PLT., 2024)
Vol. 32 No. 2